Statistical analysis of locked mode induced disruption in EAST - Wei-Ran Zhou; Guo-Hong Deng; You-Wen Sun; Hui-Hui Wang; Deng Zhou; Tong-Hui Shi; Shuai Gu; Cheng Ye; Qun Ma; Qing Zang; Kai-Yang He; Da-Long Chen; et al. (AIP Advances, 2024)
The effects of key parameters on locked mode induced disruption (LMiD) are investigated in EAST experiments. The experimental data for locked mode are collected from 2015 to 2022 when the externally applied resonant magnetic perturbation is successfully employed in EAST. In this dataset, ∼42% of the total shots are LMiD, while the remaining 58% are LM without disruption. To better analyze the LMiD, an intuitive physical process is proposed. The LMiD process can be divided into two stages, the evolution of magnetic islands and the loss of plasma stored energy. The LMiD can also be related to the evolution of the other 8 physical quantities. On the basis of this physical process analysis, the time scale and the influencing factors for LMiD are investigated using statistical analysis. It is found that the density (ne), the distance from the magnetic island outer boundary to the plasma last closed surface (dedge), the loop-voltage (Vloop), and the plasma core electron temperature (Te), which are consistent with the intuitive physical model, are key parameters to LMiD. In addition, other potentially important parameters, the relevant reasons, and statistical analysis on the parameter intervals where rapid disruption with greater harmfulness occurred have also been investigated.